Good Influence Corporate Governance , Return on Assets and Earnings Per Share in Increasing the Value of State-Owned Enterprises in Indonesia - Wanda Pramestika; Taufik Akbar (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG), Return on Assets (ROA), and Earnings Per Share (EPS) on firm value in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange. The study employs a quantitative approach using an associative method. The data used are secondary data obtained from the financial statements and annual reports of SOEs for the 2021–2023 period. The research sample was determined using a purposive sampling method, resulting in 20 SOEs as the sample. Data analysis was conducted using multiple linear regression with the assistance of statistical software. The results show that partially, GCG, ROA, and EPS do not have a significant effect on firm value. Simultaneously, these three independent variables also do not have a significant effect on firm value. The coefficient of determination (R²) of 0.054 indicates that GCG, ROA, and EPS explain only 5.4% of the variation in firm value, while the remaining variation is influenced by other factors outside the research model. These findings indicate that the firm value of SOEs is more strongly influenced by external factors such as macroeconomic conditions, government policies, and market sentiment than by the governance and financial performance indicators examined in this study.